At eternity's gate [videorecording (DVD)] - Schnabel, Julian, 1951-; Schnabel, Julian, 1951-; Dafoe, Willem; Friend, Rupert; Isaac, Oscar (Lionsgate Home Entertainment, 2019)
The last years of the great French painter Vincent van Gogh are dramatized. The focus is on the time the artist spent in Ales and Auvers-sur-Oise, France. The art of painting itself and the painter's relationship with the concept of infinity are central themes. Not an exhaustive overview of all events in the final years of Van Gogh's life, but focuses on key elements the artist experienced as he struggled with mental turmoil and produced some of his greatest masterpieces.